Mitochondrial release of AIF and EndoG requires caspase activation downstream of Bax/Bak-mediated permeabilization - Arnoult, Damien (Oxford University Press, 2003)
Mitochondrial outer-membrane permeabilization by pro-apoptotic Bcl-2 family members plays a crucial role in apoptosis induction. However, whether this directly causes the release of the different mitochondrial apoptogenic factors simultaneously is currently unknown. Here we report that in cells or with isolated mitochondria, pro-apoptotic Bcl-2 proteins cause the release of cytochrome c, Smac/Diablo and HtrA2/Omi but not endonuclease G (EndoG) and apoptosis-inducing factor (AIF). In cells treated with Bax/Bak-dependent pro-apoptotic drugs, neither the caspase inhibitor zVAD-fmk nor loss of Apaf-1 affected the efflux of cytochrome c, Smac/Diablo and HtrA2/Omi, but both prevented the release of EndoG and AIF. Our findings identify the mitochondrial response to pro-apoptotic stimuli as a selective process leading to a hierarchical ordering of the effectors involved in cell death induction. Moreover, as in Caenorhabditis elegans, EndoG and AIF act downstream of caspase activation. Thus EndoG and AIF seem to define a ‘caspase-dependent’ mitochondria-initiated apoptotic DNA degradation pathway that is conserved between mammals and nematodes.